2018
DOI: 10.1111/ijd.14008
|View full text |Cite|
|
Sign up to set email alerts
|

Onychoscopic evaluation of onychomycosis in a tertiary care teaching hospital: a cross‐sectional study from South India

Abstract: Onychoscopy, being handy, inexpensive, and noninvasive, has the potential to reduce the invasive procedures. Statistically significant patterns in DLSO and total dystrophic onychomycosis (TDO) are described in our study. Few new patterns have been described whose significance has to be tested by conducting larger sample size studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 8 publications
5
16
1
Order By: Relevance
“…Chetana et al described bluish streaks and globules and bluish gray globules as new dermoscopic observations in onychomycosis. [ 16 ] We did not notice such patterns in this study, probably because of small sample size.…”
Section: Discussioncontrasting
confidence: 61%
“…Chetana et al described bluish streaks and globules and bluish gray globules as new dermoscopic observations in onychomycosis. [ 16 ] We did not notice such patterns in this study, probably because of small sample size.…”
Section: Discussioncontrasting
confidence: 61%
“…In our study, longitudinal stria was the predominantly observed pattern (n=31, 68.75%) in DLSO, which is in accordance with the previous reports [8-12]. This pattern may be the result of the dermatophyte invasion along the nail plate; in addition, discoloration may be secondary to colony formation, flakes, or subungual debris [9, 10].…”
Section: Resultssupporting
confidence: 92%
“…The linear edge pattern without any indentations has been consistently associated with traumatic onycholysis [8, 9, 12]. This dermatoscopic finding is used to differentiate onychomycosis from traumatic onycholysis [8, 9, 12].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, males (78.3%) outnumbered females; this was similar to the findings of Yorulmaz et al (5). However, a female preponderance of onychomycosis has been reported in few other studies (6)(7)(8). Male preponderance in this study may be due to the fact that the majority of patients were agricultural workers (26.7%), followed closely by semiskilled workers (drivers, shopkeepers, masons, mechanics, cooks, or barbers) at 23.3%; both of these are male-dominated occupations in this part of India.…”
Section: Discussionsupporting
confidence: 92%